Second primary squamous cell carcinoma of the oral cavity: a retrospective cohort study of therapeutic procedures and oncological outcome - Moratin, Julius; Maas, Theresa; Horn, Dominik; Semmelmayer, Karl; Zittel, Sven; Oehme, Marcel; Engel, Michael; Hoffmann, Jürgen; Freudlsperger, Christian; Freier, Kolja; Ristow, Oliver (Clinical oral investigations, 2024)
In the presented study, the occurrence rates of second primary oral carcinomas and their prognostic relevance were analyzed.
Online veröffentlicht: 26. März 2024
Gesehen am 04.09.2024